European industry and finance face world competition - PRODI, R. (PSL Quarterly Review, 2013)
The paper, presented as the “Jean Monnet Lecture” at the European University Institute in Florence on March 20th, 1998, evaluates the current situation and perspective of European industry and finance in the face of world competition. In the context of the European Economic and Monetary Union, the author, Italian Prime Minister Romano Prodi, proposes strategic guidelines for European industrial policy. He suggests that the economic integration should force the industry and finance sectors to reconsider their roles, and that it should be coupled with political integration to be more effective. JEL Codes: F15, O11, F02